2020
DOI: 10.1109/jphot.2020.3015740
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Au/ZnO-NA Plasmonic SERS Signal Using Principal Component Analysis as a Machine Learning Approach

Abstract: In this work, we modeled a novel approach to enhance surface-enhanced Raman scattering (SERS) signals using principal component analysis (PCA) as a machine learning approach. Zinc oxide nanoarrays (ZnO-NAs) were synthesized using a hydrothermal method followed by zinc oxide nucleation on ITO glass substrates via an oxidation furnace at 500°C. The surface morphology was improved by short rapid thermal annealing (S-RTA) after deposition of a gold layer via a thermal evaporator to avoid chemical contamination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…en, the given signal matrix is X((x i ), i � 1, 2, 3, ..., n), where x i is the row vector of X [12]. Its mean vector is…”
Section: Information Sensormentioning
confidence: 99%
“…en, the given signal matrix is X((x i ), i � 1, 2, 3, ..., n), where x i is the row vector of X [12]. Its mean vector is…”
Section: Information Sensormentioning
confidence: 99%
“…The combination of machine learning analysis tools and multipotonic effects has enormous potential in data interpretation. Gupta et al used Principal Component Analysis (PCA) as a learning machine to improve SERS signals [80]. The use of PCA in this research was able to increase the SERS signal to be up to three times higher.…”
Section: Application Of Spr Technology For Sars-cov-2 Detection and A...mentioning
confidence: 84%
“…Thereafter, the SERS spectra were analyzed using PCA to determine the relationship between the molecular structures of the isomers and conductance. PCA is a multivariate statistical analysis technique that can identify the major directions of variation in a given data set. Intercorrelated quantitative dependent variables can be extracted from complex data by PCs. , Through the PCA of the SERS spectra, it was found that the third principal component (PC3) suitably reflected the isomerization behavior (Figure b,c), whereas PC1 and PC2 reflected the spectral background and the dominant MC isomer, respectively (Section 8 in the Supporting Information). The prominent peak at 1610 cm –1 in the loading vector of PC3, corresponding to the indole C–C stretching vibration of SP, is shown in Figure b, indicating that the discrimination between the SP- and MC-SMJs can be achieved via PC3.…”
Section: Resultsmentioning
confidence: 99%